Role of eIF4A proteins in miR-122 mediated Hepatitis C virus regulation - Ahmed, Choudhary-Shoaib (2017)
An estimated 2-3% of the global population is living with Hepatitis C virus (HCV) infection and 60-90% of these infections become chronic, which could leads to cirrhosis and liver cancer. While new antiviral therapies are emerging, a better understanding of how HCV interacts with host cells is important. HCV is a hepatotropic positive sense RNA virus. The HCV 5’ untranslated region (UTR) contains two binding sites for a highly abundant liver-specific microRNA, miR-122. In contrast to the canonical function for microRNAs in binding to 3’UTR sites, leading to mRNA degradation and translational repression, HCV uses miR-122 as an essential positive regulator of viral replication. The mechanism of this regulation remains uncertain, with viral translation, RNA stability and replication all implicated in different studies. In order to understand the mechanism of HCV regulation by miR-122, it is important to identify the host protein factors involved in this regulation. This thesis investigates the role for eukaryotic initiation factor 4A (eIF)4AII, which preliminary studies implicated in HCV replication and which has also been shown to function in miRNA activity. eIF4AI and eIF4AII are ATP-dependent helicases, which linearize secondary structures present in the 5’ UTR of an mRNA and help ribosome binding to the mRNA and scanning for initiation codon. Eukaryotic initiation factor (eIF)4AII has been described as a binding partner of HCV RNA polymerase enzyme (NS5B) by binding to NS5B’s C-terminal residues and is also involved in miRNA regulation of translation at 3’UTR sites. eIF4AI and eIF4AII have more than 90% sequence similarity due to which these proteins have long been functionally interchangeable. However, eIF4AII depletion had no effect on cellular growth while eIF4AI depletion was shown to be inhibitory to cellular growth. Unlike eIF4AII, eIF4AI role in miRNA regulation at 3’UTR sites is unknown. In this thesis, depletion of eIF4AII is shown to lead to a reduction in HCV RNA level, while eIF4AI knockdown had variable effects on HCV RNA levels. These variabilities could be due to the subtle differences in the confluence levels of cells or due to the experimental variability. These findings also support the idea that eIF4AI and eIF4AII function differently. In order to study whether this reduction in HCV RNA levels in eIF4AII depleted cells is linked with miR-122 regulation of HCV, sequestration, and overexpression of miR-122 in eIF4AII depleted cells were performed. We have been able to show that the presence or absence of miR-122 did not change the HCV RNA levels in eIF4AII depleted cells, which suggests that eIF4AII contribution to HCV replication is linked with miR-122 regulation of HCV and functional eIF4AII is required for miR-122 mediated regulation of HCV. However, eIF4AII did not affect miR-122 regulation of luciferase reporters in which the HCV 5'UTR controls luciferase translation. By co-immunoprecipitation, eIF4AII is shown to interact with HCV RNA and miR-122 in a miR-122-dependent manner. eIF4AII also interacts with miR-21 and miR-26a, but this interaction is not dependent on miR-122, indicating that miR-122 is specifically required for the eIF4AII-HCV RNA interaction. DDX6 and eIF4AII have been proposed to be involved in miRNA mediated repression by Ccr4-Not complex via CNOT1. The involvement of eIF4AII in miRNA mediated repression was questioned in a different study in which the interaction between eIF4AII and CNOT1 was not confirmed. siRNA based knockdown of CNOT1 reduces both HCV RNA and miR-122 co-immunoprecipitation with eIF4AII, which indicates that Ccr4-NOT complex component CNOT1 contributes to eIF4AII association with miR-122 and HCV and may be part of the same complex. Taken together, eIF4AII is identified a new host factor that is important for HCV replication, and that requires miR-122 to interact with HCV RNA, but it was not possible to demonstrate conclusively that eIF4AII regulates HCV by modulation of miR-122 activity.